Macromolecular crystallography. - Carter, Charles W.; Sweet, Robert M. (Methods in enzymology, 2003)
Accurate molecular structures are vital for rational drug design and for structure-based functional studies directed toward the development of effective therapeutic agents and drugs. Crystallography can reliably predict structure, both in terms of folding and atomic details of bonding. * Methodological methods in crystals * Methodological methods data analysis.